2011
DOI: 10.1002/cbic.201000470
|View full text |Cite
|
Sign up to set email alerts
|

A G‐Quadruplex Aptamer Inhibits the Phosphatase Activity of Oncogenic Protein Shp2 in vitro

Abstract: Shp2 is a member of the protein tyrosine phosphatase (PTP) family, which regulates a variety of cellular processes including cell growth, differentiation, mitotic cycle, and oncogenic transformation. Using a recombinant Shp2-GST protein as the target and GST as a counter target, we have identified two classes of single-stranded DNA aptamers that selectively bind to Shp2 with a K(d) in the nanomolar range. Structural studies of the most abundant sequence in the enriched library, HJ24, revealed a parallel G-quad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 56 publications
(41 reference statements)
2
29
0
1
Order By: Relevance
“…The observed stronger adhesion between the probe and the substrate in the presence of 60 mM K + is further confirmed by our CD measurement. 51 Notably, for HJ24 in the absence of K + , peak I at 16.9 pN and peak II at 39.0 pN, Figure 5b, are close to that of control DNA at 27.5 pN and HJ24 in the presence of K + at 49.7 pN, respectively, although both are shifted toward lower values. The peak area ratio for peak I and II is 1:3.…”
Section: ■ Experimentssupporting
confidence: 56%
“…The observed stronger adhesion between the probe and the substrate in the presence of 60 mM K + is further confirmed by our CD measurement. 51 Notably, for HJ24 in the absence of K + , peak I at 16.9 pN and peak II at 39.0 pN, Figure 5b, are close to that of control DNA at 27.5 pN and HJ24 in the presence of K + at 49.7 pN, respectively, although both are shifted toward lower values. The peak area ratio for peak I and II is 1:3.…”
Section: ■ Experimentssupporting
confidence: 56%
“…In Figure 2a , we showed the most probable secondary structures of these aptamers, taking into account the lower free energy (ΔG). Because many of the aptamers described in the literature contain G-quadruplex structures, 22,23,24 which strongly stabilize the tertiary structure, the capacity of apMNK2F and apMNK3R to form G-quadruplex structures was studied using the QGRS Mapper program. The analysis results indicated that the aptamer apMNK2F could form two of these structures, one with three and one with two flat planes, while apMNK3R could form a two plane G-quadruplex structure ( Figure 2a ).…”
Section: Resultsmentioning
confidence: 99%
“…Aptamers must ideally have a high stability, important for applications in biological systems in order to reach their target proteins without being degraded. Many of the aptamers described in the literature contain G-quadruplex structures, [32][33][34] which strongly stabilize the tertiary structure. Interestingly, ApTLR#1RT exhibits relatively high free energy but, eventually, it would be able to form a G-quadruplex structure.…”
Section: Discussionmentioning
confidence: 99%